Improving Contractors' Practices of Industrialized Building System (IBS) Implementation in Construction Industry - Narimah Kasim,; Mohamed Hamid Al-Shami,; Aryani Ahmad Latiffi,; Magaji Umar Ibrahim,; Rozlin Zainal,; Hamidun Mohd Noh, (Journal of Technology Management and Business, 2019)
Abstract: Nowadays, the Malaysian construction industry is moving forward to roll out technology advantage across project life-cycle for enhancing human development skills. Therefore, the government has adopted industrialized building systems (IBS) to enhance control and balance of workforce supply for overall project performance achievement. However, the challenges faced by the construction industry such as delay the completion of construction projects was due to poor contractors' practices. In addition, there are significant challenges related to contractors' practices for instance shortage of skill, practical know-how, worker capability, and financial difficulties in IBS implementation. Therefore the purpose of this study was to identify current practices and influencing factors of contractors' practices for IBS implementation in the construction industry. This study also determines the improved ways of contractors' practices for IBS implementation in the construction industry. The study was conducted in Johor Bahru, Johor where various development and construction activities are currently active. Quantitative method was conducted by distribution the questionnaires to Grade 7 (G7) contractors as study respondents which involved wide practices of IBS construction projects. Data collected were analysed using the Statistical Package for the Social Science (SPSS) 22.0 software. The study reveals that, the problems faced by contractors in their practices of IBS implementation such as low productivity, management aspects, and financial problems. Therefore, training to labour, IBS instruction guideline and improving finance, and procurement mechanism are the top recommended factors to improve contractors' practices for successful IBS implementation. In conclusion, with the improvement of contractors' practices, the productivity of IBS implementation in the construction industry can be improved.